A literature review on intervention programs for diabetic foot care - Firdaus, Mohd Khairul Zul Hasymi; Jittanoon, Piyanuch (Elsevier, 2021)
This literature review conducted to explore the best available intervention for diabetic foot care. Online databases (ProQuest, CINAHL, Science Direct and Google Scholar) were searched to retrieve relevant articles. The keywords diabetic foot care, diabetic foot care program, diabetic foot care intervention, diabetic foot education were used for data retrieval and PICO analysis. After screening analysis was completed, only 15 (from 7423) articles, published within 2007-2017, were included in a qualitative synthesis of the data. The articles were categorized as: systematic review (n=1), randomized control trial (n=3), quasi-experimental (n=3), pre-test-post-test (n=4), cohort (n=2), cross-sectional (n=1) and surveys (n=1). Themes synthesized from the analysis were: effective approach (group or individual), project leader, specialized skills required and adaptation of technology. A combination of identified approaches would help design a technology-friendly program for managing diabetic foot care.